An introduction to Antonio Gramsci : his life, thought and legacy - Hoare, George, 1984-; Sperber, Nathan, 1986- (Bloomsbury, 2016)
"This is a concise introduction to the life and work of the Italian militant and political thinker, Antonio Gramsci. As head of the Italian Communist Party in the 1920s, Gramsci was arrested and condemned to 20 years' imprisonment by Mussolini's fascist regime. It was during this imprisonment that Gramsci wrote his famous Prison Notebooks - over 2,000 pages of profound and influential reflections on history, culture, politics, philosophy and revolution. An Introduction to Antonio Gramsci retraces the trajectory of Gramsci's life, before examining his conceptions of culture, politics and philosophy. Gramsci's writings are then interpreted through the lens of his most famous concept, that of 'hegemony'; Gramsci's thought is then extended and applied to 'think through' contemporary problems to illustrate his distinctive historical methodology. The book concludes with a valuable examination of Gramsci's legacy today and useful tips for further reading. George Hoare and Nathan Sperber make Gramsci accessible for students of history, politics and philosophy keen to understand this seminal figure in 20th-century intellectual history."--